Vegetación remanente del Qhapac Ñan y la hacienda Llumahuango, sur-oriente de Quito, Ecuador. - Cerón Martínez, Carlos Eduardo (2025)
The Qhapaq Ñan or royal road of the Incas, as well as the centuriesold constructions, are part of the patrimonial assets, and the biotic resource is of scientific and historical importance, subject to research in order to make appropriate conservation and management decisions. In order to learn about the flora of the Qhapaq Ñan and the Llumahuango estate on the Quito-Mejía canton border, province of Pichincha, estate coordinates: 00°22.33’S - 78°32. 04’W, altitude 2860 m, vegetation formation: humid montane scrubland, between the months of march and august 2024, we walked the surrounding trails, herborizing at least one specimen per species, taxonomically identified and mounted on standard cardboards, which rest in the herbarium QAP. The results found are: 188 species, corresponding to 151 genera and 72 families; according to habit: 27 trees, 35 shrubs, 14 vines, 3 parasites, 11 epiphytes, 4 subshrubs, 82 herbs; by status, 126 native, 43 introduced, 11 endemic: Aegiphila ferruginea, Fuchsia loxensis, Gynoxys hallii, Miconia papillosa, Oligactis pichinchensis, Oreopanax ecuadorensis (Least Concern), Ageratina sodiroi, Calceolaria sericea, Jungia mitis, Kingianthus paniculatus, Geissanthus pichinchae (Near Threatened). The most frequent families: Asteraceae, Solanaceae, Fabaceae, Poaceae, Polypodiaceae and Polygonaceae; it also includes pastures, chacras with cereals, vegetables and specerias, as well as introduced trees, mainly Eucalyptus globulus. Although the hacienda is a heritage site with more than 100 years of existence, territory that crosses the Qhapaq Ñan, both are at risk of disappearing along with the native and endemic vegetation of the streams and borders of the private properties, due to accelerated urban expansion and the struggle of economic interests, as well as the breakdown of the water cycle at the ridgeline.